Proposed Workstation Design in Laboratory for Musculoskeletal Disorder Complaints - Saptiansyah, Refaldi; Haqi, Dani Nasirul; Juwono, Kholifah Firsayanti (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction:Laboratory is a means of improving the effectiveness of learning. The problem faced by laboratory staff in performing their work (analysis and experimentation) is fatigue caused by long work time with inappropriate sitting posture and position. The use of a wooden chair without a backrest and with a seat height that is too high or too low can cause musculoskeletal disorders (MSDs). This study aims to provide a workstation design suggestion with attention to ergonomics to reduce complaints of musculoskeletal disorders. Method: This descriptive research used an observational method. The population in this research consisted of 31 female students of a feed laboratory user, and the sample consisted of 16 respondents at the SIKIA Laboratory. Data collection for this study was conducted from July to September 2022. The independent variable in this study was the dimension of the workstation, and the dependent variable was musculoskeletal complaints. Result: Anthropometric measurements on laboratory assistants of the SIKIA Laboratory showed that the average popliteal height was 53.25 cm. Assessment on musculoskeletal disorder complaints shows that most complaints are found on "Pain in the back” with a score of 36. A new chair and table design is proposed, where the width of the seat back is 39.75 cm. Conclusion: A new workstation design is proposed that focuses on ergonomics to reduce the complaints of musculoskeletal disorders.